L-GLUTAMINE SUPPLEMENTATION ASSOCIATED WITH MODERATE AEROBIC TRAINING IMPROVES BIOMETRIC, GLYCEMIC PROFILE AND THE ANTIOXIDANT DEFENSE - Bender dos Santos, Analú; Corrêa Costa-Beber, Lílian; de Pelegrin Basso, Eloisa Gabriela; Brendler Goettems Fiorin, Pauline; Bueno Basso, Renan Daniel; Machado Sulzbacher, Maicon; Ludwig, Mirna Stela; Heck, Thiago Gomes (Revista Contexto & Saúde, 2020)
Introduction: L-glutamine is a non-essential amino acid, whose intrinsic pool of appears to be depleted during catabolic conditions, such as intense or high duration exercise, and to avoid the exercise- related benefits. Therefore, its supplementation could provide an additional source of L-glutamine and prevent these effects. However, the oral intake of its free form has been discouraged, despites of some evidences reporting positive effects. Objective: to verify whether the L-glutamine supplementation (in its free form) could provide an additional improvement in biometric, glycemic and redox parameters, in animals undergoing moderate aerobic training (MAT). Methods: 28 Swiss male mice were divided into four groups: Cont (n=7), Ex (n=7), Glut (n=8), and Ex+Glut (n=6). Glut and Ex+Glut received gastric gavage of L-glutamine (1g/kg), while Cont and Ex groups received 100 µL of PBS one hour before exercising, five days/week, six weeks. Ex and Ex+Glut underwent moderate swimming, while Cont and Glut remained sedentary, for the same period. Mice started swimming with 2% of body weight attached to the tail during 20 min, and ended the experiment with 4% during 60 min. Results: L-glutamine supplementation increased the gastrocnemius mass and improved the glucose tolerance in animals submitted to MAT. It improved the antioxidant status in gastrocnemius, liver and pancreas, and declined it in adipose tissue in animals undergoing MAT. The drop of adipose antioxidant defense was associated with adiposity, while pancreas antioxidant activity was inversely associated with the glucose intolerance. Conclusion: L-glutamine (free form) improves biometric and glucose parameters, and enhances antioxidant activities.